PAYMENT AGREEMENT SYSTEM FOR NON-CASH PRODUCT PURCHASES AT PT WINGS FOOD ACEH BESAR ACCORDING TO BA'I AL-DAYN CONTRACT - Al Ghifari Fauzi; Hajarul Akbar (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2026)
This study aims to analyze the payment agreement system for non-cash product purchases implemented by PT Wings Food Aceh Besar from the perspective of the ba'i al-dayn contract. The research uses a qualitative method with a normative sociological approach, through interviews with suppliers and a literature review. The results of the study show that the non-cash payment system provides access to capital for small traders without the addition of interest, so that it is in line with the basic principle of ba'i al-dayn. However, this practice also contains potential gharar due to the uncertainty of repayment when traders reorder before the previous obligation is settled. The findings of this study confirm the importance of strengthening risk management, especially through the establishment of receivables limits and gradual settlement schemes, to ensure that transactions remain in accordance with the principles of muamalah and are sustainable for both parties. This research is expected to contribute to expanding the study of the application of the ba'i al-dayn contract to modern distribution trade practices.